Green Growth, Green Profit how green transformation boosts business - Berger, Roland (Houndmills Palgrave Macmillan, 2011)
Green technology is a multi-billion-dollar business with enormous growth potential, Green Growth,Green Profit-How Green Transformation Boosts Business is the authoritiative guide for managers for navigating the tectonic shift taking place in the business world as a result of the megatrends of population growth, globalization, urbanization, and climate change. Companies need to swtich to a sustainable business model to survive. This highly accessible volume shows how companies can adapt their business model and accomplish the green transformation to profit from the changing conditions and gain an edge over competition. Pioneering insights from partners at Rolan Berger Strategy Consultants can help managers to recognize the challenges ahead and devise strategies about how to proceed at this critical juncture. This book outlines in detail how companies can redesign products, processes, and whole systems to generate ecological and economic sustainability. Companies will profit from the new imperative for green solutions by substituting existing technologies, increasing efficeincy, and recycling-in its broadest sense. The authors turn a spotlight on the ten most important regions worldwide, and explain how these should respond to key technologies such as renewable energy, e-mobility, and energy, as well as pointing out highly promi areas of growth.
Includes bibliographical references (p. 251-255)
Keywords: Sustainable development. Industries --Environmental aspects. Environmental policy --Economic aspects. Energy development --Environmental aspects